Antifungal Activity of Morinda citrifolia leaf extracts against Colletotrichum acutatum - Oktira Roka Aji; Larasati Haliimah Roosyidah (Biogenesis: Jurnal Ilmiah Biologi, 2020)
Anthracnose is a plant disease that can infect a variety of plants worldwide. Fungal pathogen groups are the cause of anthracnose, one of which is Colletotrichum acutatum. Morinda citrifolia is famous for having antimicrobial activity. This study aims to determine the antifungal activity of M. citrifolia leaves extract against the growth of the fungus C. acutatum. The extract solvent used was 96% ethanol. The experiment consisted of five treatments (0%, 20%, 40%, 60% and propineb 0.1% as positive control). The method used in this study was the poisoned food technique. In this technique, C. acutatum was grown on PDA media mixed with M. citrifolia leaves extract. Antifungal activity was observed based on reduced mycelium growth compared to control. Observations were made every day by measuring the diameter of the fungus mycelium for eleven days. The analysis showed that 60% M. citrifolia leaves extract effectively inhibited the growth of the mycelium C. acutatum on the eleventh day of observation.